EDUKASI ACTIVITY DAILY LIVING PADA PENDERITA OSTEOARTHRITIS KNEE DI KELURAHAN TALANG BANJAR - Indah Permata Sari; Wanti Hasmar; Faridah Faridah (LPPM Universitas Abdurrab, 2022)
ABSTRACT Osteoarthritis is a progressive degenerative joint disease in which the cartilage that protects the ends of the bones begins to break down, causing pain and loss of mobility. Osteoarthritis is one of the complaints that can be treated by physiotherapy. Physiotherapy program in education activity daily living osteoarthritis aims to improve functional abilities so that they can carry out activities as usual, reduce impairment and improve function, protect joints from further damage. Activity daily living education for knee osteoarthritis includes stretching exercises, flexibility exercises, and osteoarthritis exercises. The method of community service activities is carried out using the lecture method, and asking questions about osteoarthritis, then distributing leaflets. The results of this educational activity are very useful for people with osteoarthritis of the knee, when given this exercise, mothers or the elderly feel happy because this activity is very useful for reducing their stiffness and pain complaints. The conclusion of this educational activity is that mothers who take part in the activity already understand exercises for osteoarthritis of the knee. Keyword: Osteoarthritis Knee, Physiotherapy, Activity Daily Living